Early Clinical Outcomes and Complications of Transfibular Total Ankle Arthroplasty: The Australian Experience - Andrew Wines MBBS; Rajat Mittal PhD; Michael Symes FRACS, MBBS, MPH; Ellery Clugston MBBS; Corey Scholes PhD; Alex Wilton MBBS (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Ankle Introduction/Purpose: We report the short-term outcomes of a retrospective cohort of Trabecular Metal total ankle arthroplasties (TAAs) via a transfibular approach from a single, nondesigner surgeon in Australia. Methods: This was a retrospective cohort study. Demographic, clinical, and patient-reported outcome measures (PROMs) were collected. The primary outcome was the Foot and Ankle Outcome Score (FAOS), and secondary outcomes included patient satisfaction, the EuroQol-5 Dimension (EQ5D), and complications including revision rates. Results: Between 2016 and 2019, 84 trabecular metal prostheses were implanted in 84 patients. Mean age (SD) at time of surgery was 68 (7.8) years, and 46 (55%) were male. Mean follow-up (SD) was 26.1 (13) months. There were significant improvements in the FAOS (Pain (47.9 to 79.1), activities of daily living (59.5 to 83.7), and quality of life (25.5 to 60.2)) and EQ-5D (0.55 to 0.75) (P < .001), and overall satisfaction was 69.6%. Complications included wound infection/breakdown (11.9%), fibular nonunion (3.5%), plate irritation (3.5%), and tibial nerve neuropathy (3.5%). There were no thromboembolic complications. Implant survivorship was 100%, with Trabecular Metal components retained in all patients. Two patients developed deep infection, with 1 requiring debridement and polyethylene exchange. No patients experienced implant loosening. Conclusion: Our results demonstrate that the trabecular metal survival rates are comparable with other total ankle implants in the Australian Orthopaedic Association National Joint Replacement Registry and as published in other international literature. Overall patient satisfaction was high, as were PROMs. However, the data highlight potential complications uniquely associated with this implant. The authors believe that these figures support TAA via a transfibular approach as a viable option in the treatment of ankle arthritis.